Recent advances in the photovoltaic applications of coordination polymers and metal organic frameworks. Issue 11 (10th February 2016) - Kaur, Rajnish; Kim, Ki-Hyun; Paul, A. K.; Deep, Akash
Abstract : Coordination polymers and metal organic frameworks (CPs/MOFs) have attracted a great deal of attention in a variety of scientific fields due to their unique and intriguing structural properties. Abstract : Coordination polymers and metal organic frameworks (CPs/MOFs) have attracted a great deal of attention in a variety of scientific fields due to their unique and intriguing structural properties. Photovoltaic applications of these porous polymers belong to a relatively new area of research. The current status of research on this subject amply highlights the usefulness of CPs/MOFs in improving the properties of next-generation photovoltaic devices ( e.g., dye-sensitized solar cells). This review article was written to cover the recent advancements that have been achieved in this rapidly expanding area of research. It also compares and contrasts the energy conversion efficiencies in photovoltaic applications using different MOFs and other systems.